The term structure of expectations - Richard K. Crump; Stefano Eusepi; Emanuel Mönch; Bruce Preston (Federal Reserve Bank of New York, 2021)
Economic theory predicts that intertemporal decisions depend critically on expectations about future outcomes. Using the universe of professional survey forecasts for the United States, we document the behavior of the entire term structure of expectations for output growth, inflation, and the policy rate. We show that a simple unobserved components model of the trend and cycle explains the joint behavior of both consensus measures of expectations and the observed disagreement among individual forecasters. Importantly, univariate models of each variable are outperformed by a multivariate model of the joint dynamics of these three variables, particularly for nominal interest rates. Consistent with the data, the model predicts a link between revisions in long-run expectations to short-term forecast errors. In structural models, learning about the long run has important empirical and theoretical implications for monetary and fiscal policy.
Keywords: D83; D84; E32; E43; E44; G12; 330; expectation formation; imperfect information; survey forecasts; shifting endpoint models; monetary policy; term premiums